Digest: Nature and nurture: Influences of parental care and rearing environment on phenotypic plasticity in Nicrophorus vespilloides. (1st March 2022) - Sun, Syuan‐Jyun; Narayan, Vikram P.; Wang, Yiguan; Wasana, Nidarshani
Abstract: What conditions favor niche expansion in nature? In the burying beetle Nicrophorus vespilloides, Schrader et al. found that larvae reared with parental care on larger carcasses were better equipped for resource use than individuals reared without parental care on smaller carcasses. This finding illustrates that developmental plasticity induced by parental care and carcass size has the potential to influence adaptive diversification.